Is Animal Welfare an Internationally Understood Concept in the Zoo World? Thematic Analysis of Two Regional Groups of Zoo Staff - Heather Bacon; Belinda Vigors; Darren J. Shaw; Natalie Waran; Cathy M. Dwyer; Catriona Bell (Animals, 2021)
Universal frameworks for zoo animal welfare have been suggested. However, there is little evidence of a cross-cultural understanding of zoo animal welfare. This paper reports themes emerging from a qualitative study of international (European and Chinese) zoo professionals on zoo animal welfare issues. Structured telephone interviews were conducted with eight Chinese and eight European zoo staff, covering aspects of zoological animal welfare, conservation and zoological husbandry practices. These qualitative data were thematically analysed, and key themes generated. This paper describes three themes relating to ‘What is animal welfare’ ‘Animal welfare frameworks’ and ‘The human element in animal welfare’. This analysis indicates that the concept of animal welfare has cultural equivalence across Europe and between Europe and China, and that zoo staff are familiar with welfare frameworks. In China, a need for senior leadership and motivating staff to improve animal welfare emerged.